The effect of jugular bulb–vestibular aqueduct dehiscence on hearing and balance. (2nd November 2015) - Li, Shufeng; Shen, Na; Cheng, Yushu; Sha, Yan; Wang, Zhengmin
Abstract: Conclusion: This study suggests that jugular bulb–vestibular aqueduct dehiscence (JBVAD) does not affect the hearing or balance functions of the inner ear. Objectives: Since JBVAD may cause impairment of the inner ear and induce hearing loss, tinnitus, and vertigo, this study was to investigate the effect of JBVAD on hearing and balance. Method: Patients undergoing temporal bone computed tomography (TBCT) scans from May 2013 to December 2013 at a tertiary referral hospital were reviewed. The topographic relationship between the jugular bulb (JB) and the vestibular aqueduct was assessed. The findings were classified as normal when there was always a bony structure between the two structures and as dehiscent when the bony coverage separating the two structures was absent. Clinical data were collected via electronic records and clinical follow-up. Results: A total of 1313 out of 8325 patients were diagnosed with a HJB. Forty-six patients showed JBVAD. The prevalence of dehiscence was 0.6% in patients undergoing temporal bone CT scans and 3.5% in patients with HJB. Of the 46 patients with JBVAD, 23 (50%) had sensorineural hearing loss, three (6.5%) had tinnitus, and two (4.3%) had vertigo. The correlation between JBVAD and these clinical symptoms did not achieve statistical significance.